ISTI‘ARAH IN SURAH AL-BAQARAH: A BALĀGHAH ANALYSIS OF QUR’ANIC METAPHORS IN CONSTRUCTING MORAL AND SPIRITUAL DISCOURSES - Dafqa Putri, Najwaturraihanah; Nabila, Salwa Duratun (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study aims to identify and analyze the types of isti‘ārah (metaphor) in Surah Al-Baqarah verses 1–266 and to explore the embedded moral and spiritual values. Isti‘ārah, as a form of rhetorical metaphor in Arabic rhetoric (balāghah), serves not only as an aesthetic element but also as a tool for delivering profound ethical and faith-based messages in the Qur'an. Using a qualitative content analysis method, this study examines various classifications of isti‘ārah based on their contextual clues (qarīnah), linguistic forms (primary and derivative), structural completeness (explicit, implicit, and absolute metaphors), and representative similes (tamtsīliyyah). The findings show that the use of isti‘ārah in Surah Al-Baqarah strengthens Qur'anic messages by evoking emotional and spiritual responses. Moral messages include warnings against betrayal and injustice (e.g., QS 2:9, 2:27), while spiritual insights are conveyed through metaphors of darkness and light or symbolic deafness and blindness (e.g., QS 2:18, 2:257). These rhetorical tools not only beautify the text but also deepen reflection and understanding of divine guidance.